Phenotypic and Genotypic Characterization and Treatment of a Cohort With Familial Tumoral Calcinosis/Hyperostosis‐Hyperphosphatemia Syndrome. (20th September 2016) - Ramnitz, Mary Scott; Gourh, Pravitt; Goldbach‐Mansky, Raphaela; Wodajo, Felasfa; Ichikawa, Shoji; Econs, Michael J; White, Kenneth E; Molinolo, Alfredo; Chen, Marcus Y; Heller, Theo; Del Rivero, Jaydira; Seo‐Mayer, Patricia; et al.
ABSTRACT: Familial tumoral calcinosis (FTC)/hyperostosis‐hyperphosphatemia syndrome (HHS) is a rare disorder caused by mutations in the genes encoding fibroblast growth factor‐23 ( FGF23 ), N ‐acetylgalactosaminyltransferase 3 ( GALNT3 ), or KLOTHO . The result is functional deficiency of, or resistance to, intact FGF23 (iFGF23), causing hyperphosphatemia, increased renal tubular reabsorption of phosphorus (TRP), elevated or inappropriately normal 1, 25‐dihydroxyvitamin D3 (1, 25D), ectopic calcifications, and/or diaphyseal hyperostosis. Eight subjects with FTC/HHS were studied and treated. Clinical manifestations varied, even within families, ranging from asymptomatic to large, disabling calcifications. All subjects had hyperphosphatemia, increased TRP, and elevated or inappropriately normal 1, 25D. C‐terminal FGF23 was markedly elevated whereas iFGF23 was comparatively low, consistent with increased FGF23 cleavage. Radiographs ranged from diaphyseal hyperostosis to massive calcification. Two subjects with severe calcifications also had overwhelming systemic inflammation and elevated C‐reactive protein (CRP). GALNT3 mutations were identified in seven subjects; no causative mutation was found in the eighth. Biopsies from four subjects showed ectopic calcification and chronic inflammation, with areas of heterotopic ossification observed in one subject. Treatment with low phosphate diet, phosphate binders, and phosphaturia‐inducing therapies was prescribed with variable response. One subject experienced complete resolution of a calcific mass after 13 months of medical treatment. In the two subjects with systemic inflammation, interleukin‐1 (IL‐1) antagonists significantly decreased CRP levels with resolution of calcinosis cutis and perilesional inflammation in one subject and improvement of overall well‐being in both subjects. This cohort expands the phenotype and genotype of FTC/HHS and demonstrates the range of clinical manifestations despite similar biochemical profiles and genetic mutations. Overwhelming systemic inflammation has not been described previously in FTC/HHS; the response to IL‐1 antagonists suggests that anti‐inflammatory drugs may be useful adjuvants. In addition, this is the first description of heterotopic ossification reported in FTC/HHS, possibly mediated by the adjacent inflammation. © 2016 American Society for Bone and Mineral Research.